Cone-beam computed tomography of bilateral radiculous maxillary first premolars - Mohammad Ahmad Alenezi; Mohammad Abdullah Tarish; Saad Al-Nazhan (Wolters Kluwer Medknow Publications, 2016)
A deep knowledge of the internal and external anatomy of various human teeth is a backbone for a successful outcome of endodontic therapy. Usually, maxillary first premolar tooth has two roots, buccal and palatal. Three-rooted maxillary first premolar is scarce. The clinician has to expect any variation in root canal system and use the best diagnostic tools to manage the cases. The aim of this case report was to illustrate bilateral three-rooted maxillary first premolars and to describe the endodontic implication in preoperative assessment and during operative procedures.